Slovenščina na dlani 1 - Ulčnik, Natalija (2018)
Slovene in the Palm of Your Hand 1. The monograph was prepared as a part of the project Slovenščina na dlani (Slovene in the palm of your hand), which focuses on preparing an interactive learning e-environment for the Slovene language, which will primarily be used in primary and secondary schools. After completion of the project, it will be freely accessible to the public. The project brings together experts of both genders from various fields (Slovene studies, linguistics, didactics, language technology, computer programming). We also developed close cooperation with Slovene teachers, pupils and students from fourteen educational institutions from all over Slovenia. We encouraged them to play an active role in designing the e-environment. We also prepared educational activities for them, which we have presented in this monograph. It offers professional novelties and answers interesting questions such as what our favourite words are, how new words are coined, why it is important to learn about phrases and proverbs, how to deal with the text, why reading literacy is important, how to get access to knowledge, which types of tasks appear in e-materials, how the textual corpus is formed and what the function of the programmer is in the preparation of the e-environment. It also provides information on project activities and responses to the early results of our work. The monograph assumes the continuation of this work. We hope that it will become a publication in which both experts and practitioners will publish their own professional contributions.
Keywords: language use; lexicology; phraseology; paremiology; textual types; reading literacy; learning methods; typology of tasks; textual corpus; e-material; learning Slovene